LEAN PROJECT MANAGEMENT: A case study of a biomass power plant project in the UK - Eto, Rodrigo (2009)
Nowadays, companies are continuously seeking to create and sustain competitive advantages to improve their performance and strength their market position. Lean philosophy has allowed organisations to confront the current and future challenges to many industries. Lean focuses on identifying and eliminating waste throughout a product or service value stream, extending not only within the organisation but also along the company’s supply chain network. The competitiveness in the UK biomass energy market has increased the pressure on players to improve their performance by developing successful projects faster. Based on the above statement, this study will adopt Lean Philosophy to analyse the management of biomass power projects in the UK with the following purposes: